Movement parties in Europe: a comparative assessment - Borbáth, Endre; Paxton, Fred (Acta politica, 2025)
Research on political parties and social movements has long developed independently, separated by the disciplinary boundaries of political science and sociology. We see the recent successes of ‘movement parties’ as a push to bridge the two disciplinary traditions in order to describe this new hybrid party type accurately. To this end, we ask to what extent and under what conditions do we observe movement parties in European party systems, and how can we define the various subtypes? In the introduction to the special issue, we make three contributions. First, we identify existing definitions and empirical examples in the study of movement parties based on a systematic review of the emerging literature. Second, we operationalize Herbert Kitschelt's influential definition of lower levels of programmatic and organizational investment coupled with a higher degree of protest mobilization. Third, we introduce the individual contributions to the special issue and situate them within the relevant theoretical debates. Utilizing a new set of quantitative indicators, we empirically assess how parties identified as movement parties in the existing literature score on programmatic, organizational, and protest dimensions. The analysis underscores the heterogeneity of movement parties, with only a few cases aligning with Kitschelt's comprehensive definition.
Online veröffentlicht: 16. Dezember 2024
Gesehen am 11.03.2025